Frequency analysis for modulation‐enhanced powder diffraction. Issue 4 (1st July 2016) - Chernyshov, Dmitry; Dyadkin, Vadim; van Beek, Wouter; Urakawa, Atsushi
Abstract : A periodic modulation of experimental conditions would affect both intensities and Bragg angles for the diffraction lines. A frequency response (a series of harmonics) has been derived analytically and compared with a simulated modulation experiment. Abstract : Periodic modulation of external conditions on a crystalline sample with a consequent analysis of periodic diffraction response has been recently proposed as a tool to enhance experimental sensitivity for minor structural changes. Here the intensity distributions for both a linear and nonlinear structural response induced by a symmetric and periodic stimulus are analysed. The analysis is further extended for powder diffraction when an external perturbation changes not only the intensity of Bragg lines but also their positions. The derived results should serve as a basis for a quantitative modelling of modulation‐enhanced diffraction data measured in real conditions.